From within the shadows of the everyday: Localized entrepreneurship and the dilemma of scale. Issue 5 (19th October 2020) - Mars, Matthew M.
ABSTRACT: Economic re-localization is widely viewed as a principal mechanism for bringing greater autonomy, democracy, justice, prosperity, and general wellness to communities. Entrepreneurial initiatives that are bounded to the localized scale are a fundamental element of the underlying localism movement. The current study uses a set of theoretical constructs pulled from everyday sociology (reflexivity, contextualism, interaction) to guide a qualitative exploration of the implications of localized scale on the routine practices and day-to-day realities of localized food entrepreneurs (LFEs) in Southern Arizona, USA and Central New Mexico, USA. The findings reveal the following four attributes that characterize the influence of localized scale on the daily lives and entrepreneurial trajectories of the LFEs included in the study: set market cap, bounded experimentation, perpetual persistence, and collective currency. The findings evoke a provocative critique of the social and economic merits of localism as an alternative path toward community development.